Effectiveness and Awareness on Tax with Increasing Regional Income Through the Mediation Role of Taxpayer Compliance - Setiadi, Iwan Kresna; Wahyudi, Wahyudi; Supriadi, Yudi Nur (Garuda Prestasi Nusantara Consulting, 2023)
This research was conducted to analyze the effectiveness of collection awareness to acquisition duty of right on land and building (BPHTB) with the improvement of regional income in Depok City. The sample in this study is BPHTB in Depok City taxpayers as many as 200 respondents with purposive sampling method. The data analysis technique used in this study is quantitative analysis using the SEM (Structural Equation Modeling) model of the AMOS 22 program. The results of this study indicate that there is a positive impact of the system of collection effectiveness, and awareness of taxpayers BPHTB on tax payer compliance the Significant increase in Regional Income. The meaning of an effective strategy in increasing regional income through the effectiveness of BPHTB tax collection and the results of calculating the direct, indirect and total influence resulting in novel values ​​from the results of the study.